The Influence of Advertising Intrusiveness and User Experience on Switching Intention through Customer Satisfaction: An Educational Management Perspective - Charli Oliver; Nurul Komari; Nur Afifah; Bintoro Bagus Purmono; Harry Setiawan (Al-Qalam Institue, 2026)
This study aims to examine the influence of advertising intrusiveness and user experience on switching intention through customer satisfaction from an educational management perspective. Employing a quantitative approach with a causal research design, data were collected through structured questionnaires using a Likert scale from 205 respondents selected through purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3.0. The findings reveal that advertising intrusiveness has a negative and significant effect on customer satisfaction and a positive and significant effect on switching intention. User experience has a positive and significant effect on customer satisfaction but does not directly influence switching intention. Furthermore, customer satisfaction has a negative and significant effect on switching intention and significantly mediates the relationship between advertising intrusiveness, user experience, and switching intention. These results suggest that intrusive advertising increases users’ intention to switch platforms, while positive user experience enhances satisfaction, which subsequently reduces switching intention. From an educational management perspective, the study highlights the importance of managing digital learning environments by minimizing intrusive elements and optimizing user experience to sustain user satisfaction and platform retention in increasingly competitive digital ecosystems.